Development and evaluation of the RapidAir® dispersion model, including the use of geospatial surrogates to represent street canyon effects. (October 2018) - Masey, Nicola; Hamilton, Scott; Beverland, Iain J.
Abstract: We developed a dispersion model (RapidAir ® ) to estimate air pollution concentrations at fine spatial resolution over large geographical areas with fast run times. Concentrations were modelled at 5 m spatial resolution over an area of ∼3500 km 2 in <10 min. RapidAir ® was evaluated by estimating NOx and NO2 concentrations at 86 continuous monitoring sites in London, UK during 2008. The model predictions explained 66% of the spatial variation (r = 0.81) in annual NOx concentrations observed at the monitoring sites. We included discrete canyon models or geospatial surrogates (sky view factor, hill shading and wind effect) to improve the accuracy of model predictions at kerbside locations. Geospatial surrogates provide alternatives to discrete street canyon models where it is impractical to run canyon models for thousands of streets within a large city dispersion model (with advantages including: ease of operation; faster run times; and more complete treatment of building effects). Graphical abstract: Image 1 Highlights: RapidAir ® dispersion model evaluated for annual NOx and NO2 in London, UK. 5 × 5 m resolution model generated for 3500 km 2 area in under 10 min. Largest underestimation at kerbside sites (annual NMB = −0.25 vs. −0.05). Inclusion of canyon models reduced NMB in street canyons (−0.14 vs. −0.18). Geospatial surrogates used to represent urban morphology over large area.